Comparative analysis of constitutes and metabolites for traditional Chinese medicine using IDA and SWATH data acquisition modes on LC-Q-TOF MS - Dian Kang; Qingqing Ding; Yangfan Xu; Xiaoxi Yin; Huimin Guo; Tengjie Yu; He Wang; Wenshuo Xu; Guangji Wang; Yan Liang (Elsevier, 2020)
Identification of components and metabolites of traditional Chinese medicines (TCMs) employing liquid chromatography-quadrupole time-of-flight mass spectrometry (LC-Q-TOF MS) techniques with information-dependent acquisition (IDA) approaches is increasingly frequent. A current drawback of IDA-MS is that the complexity of a sample might prevent important compounds from being triggered in IDA settings. Sequential window acquisition of all theoretical fragment-ion spectra (SWATH) is a data-independent acquisition (DIA) method where the instrument deterministically fragments all precursor ions within the predefined m/z range in a systematic and unbiased fashion. Herein, the superiority of SWATH on the detection of TCMs' components was firstly investigated by comparing the detection efficiency of SWATH-MS and IDA-MS data acquisition modes, and sanguisorbin extract was used as a mode TCM. After optimizing the setting parameters of SWATH, rolling collision energy (CE) and variable Q1 isolation windows were found to be more efficient for sanguisorbin identification than the fixed CE and fixed Q1 isolation window. More importantly, the qualitative efficiency of SWATH-MS on sanguisorbins was found significantly higher than that of IDA-MS data acquisition. In IDA mode, 18 kinds of sanguisorbins were detected in sanguisorbin extract. A total of 47 sanguisorbins were detected when SWATH-MS was used under rolling CE and flexible Q1 isolation window modes. Besides, 26 metabolites of sanguisorbins were identified in rat plasma, and their metabolic pathways could be deduced as decarbonylation, oxidization, reduction, methylation, and glucuronidation according to their fragmental ions acquired in SWATH-MS mode. Thus, SWATH-MS data acquisition could provide more comprehensive information for the component and metabolite identification for TCMs than IDA-MS.